Pengelompokkan Kecamatan Berdasarkan Potensi Pertanian di Kabupaten Halmahera Selatan dengan Analisis Gerombol - Meilissa Harikadua; Djoni Hatidja; Charles E Mongi (Sam Ratulangi University, 2020)
This study aims to classify sub-districts based on the potential of agricultural, plantation, livestock, marine fisheries and forestry commodities in the area of South Halmahera Regency. The data used in this study are secondary data taken from the website of the Central Statistics Agency of South Halmahera Regency.The analysis used in this study is Cluster Analysis with a single linkage method and the results obtained are the formation of 3 cluster including Cluster 1 consisting of 28 districts namely: South Obi, Obi, West Obi, East Obi, North Obi, Bacan , South Mandioli, North Mandioli, Batang Lomang Islands, South East Bacan, Middle East Bacan, West Bacan, West Kasiruta, East Kasiruta, North West Bacan, Kayoa, West Kayoa, South Kayoa, North Kayoa, Makian Island, Makian Barat, Gane West, South West Gane, North West Gane, Joronga Islands, East Gane, Middle East Gane and South East Gane. Cluster 2 consisted of South Bacan sub-district and Cluster 3 consisted of East Bacan sub-district.